Conscious Ergonomics in Architecture: Energy, Matter, and Form from Theory to Practice - Araya-Leon, M (Springer Science and Business Media Deutschland GmbH, 2021)
Given the importance of how the built environment influences the well-being and health of people in a positive or negative way, in addition to the need of expanding this field of knowledge, this work teaches the model of “Conscious Ergonomics” in Architecture, which proposes a holistic and systemic view to contribute to integral well-being. Formed by the trinomial energy, matter, and form as articulators of perceived and unperceived information. For the above, a mixed method is developed comprising the state of scientific art and various empirical experiences. As results, the most representative parameters of each dimension –the built environment and the human being– are defined, which, depending on their level of relationships, respond better to this holistic vision. It is seen as an opportunity to strengthen the formal, energetic, and biophilic aspects, the exploration in commercial and industrial contexts, and the link with more objective studies on the human being and its biological responses. Finally, this research seeks to codify knowledge for new evidence-based architectural design strategies. © 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.